how to solve x(x-x) = (x+x) (x-x)
please answer me immediatly because i'm tired from thinking..
Solve it and i'm going to be thankfull
if x power 2 - x power 2 = x power 2 - x power 2
x(x-x) = (x-x) (x+x)
1x = 2x
1 = 2
Something is wrong, what is it? please answer me immediatly..
2 Answers | Add Yours
x(x-x) = (x+x)(x-x).
x^2-x^2 = x^2-x^2 is correct
But x(x-x) = (x+x)(x-x) is correct
But x = x+x is not correct as we committed the error of division by zero and arrived at the wrong result.
That is why we say an equation can be solved by adding or subtracting equals, multiplying or dividing by equals both sides but with a restriction not to multiply nor to divide by zero.
We have to solve x(x-x) = (x+x) (x-x)
First, if you see the terms on the left, you have x*(x-x) . Now (x-x) =0 , and anything multiplied by zero is zero.
Also, on the right side you have (x+x)*(x-x). Again (x-x) =0, which makes (x+x)*(x-x) equal to zero.
It is not possible for you to cancel terms that equal 0 on both the sides and try to equate the terms that are left.
That is, you cannot divide both sides of the equation x(x-x) = (x+x) (x-x) by (x-x) to get x= (x+x) as the division involves dividing 0 by 0 which is not defined.
Remember that 0/0 is not equal to 1 but it is not defined and hence the operation cannot be performed.
We’ve answered 319,807 questions. We can answer yours, too.Ask a question